The Alevi-Bektashi Belief System According to Turkish Nationalists: Nevşehir as a Sample Case - Şahin, Yasin (Journal of Alevism-Bektashism Studies, 2025)
A review of the existing literature on the subject reveals that studies in Turkey concerning social cohesion and belief systems have predominantly been framed within the Alevi-Sunni axis. Moreover, researches examining Turkish nationalists’ perspectives on the Alevi-Bektashi belief system and community has largely been based on the views of intellectuals, without incorporating fieldwork. This study addresses this gap by conducting field research in the province of Nevşehir, where Turkish nationalist sentiment is known to have strong social representation. In-depth interviews were conducted with 22 participants. The study aims to explore Turkish nationalists’ views on the Alevi-Bektashi belief system and community, and to identify the key problems concerning social cohesion.For this purpose, a qualitative research method was employed, specifically adopting a phenomenological research design. Based on this methodology and design, fieldwork was carried out, and semi-structured interviews were conducted with 22 Turkish nationalists selected through purposive and snowball sampling methods. Audio recordings were taken with participants’ consent, transcribed with the help of software, and then permanently deleted. The data were collected using a semi-structured interview form. The transcribed data were analyzed using content analysis, from which codes, categories, and themes were identified, leading to key findings. The tables created through content analysis were further interpreted using descriptive analysis.The study found that a significant majority (82%) of Turkish nationalists hold positive views toward the Alevi–Bektashi belief system and community. According to Turkish nationalists, Alevism is perceived as a community, a sect, a belief system, a way of thought, a concept, an ideological idea, and a path. Bektashism, on the other hand, is seen as a religious order (tariqa), a community, a concept, a system of thought, a sect, and a cultural structure. From the perspective of Islam, the majority of Turkish nationalists (83%) consider the Alevi–Bektashi belief system to fall within the scope of Islam. Culturally, they perceive the Alevi–Bektashi tradition and community as reflecting Turkish culture.
Keywords: Nationalism; Turkish Nationalism; Alevi–Bektashi Belief System; Society; Social Cohesion